Ciphertext-only attacks and weak long-term keys in T-310. Issue 4 (4th July 2018) - Courtois, Nicolas T.; Oprisanu, Maria-Bristena
ABSTRACT: T-310 is an important Cold War cipher (Schmeh2006 ). It was the principal encryption algorithm used to protect various state communication lines in Eastern Germany in the 1980s. The cipher is quite robust, and it outputs extremely few bits from the internal state. In this article, the authors study the choice of the long-term key in T-310. They show that if a key is faulty, for example if they omit to check just one condition which the keys should satisfy, and more or less each time the round function is not bijective, communications can be decrypted in a ciphertext-only scenario. The authors provide mathematical proofs that the main historical key classes KT1 and KT2 are secure against such attacks.